Remittances and Current Account Balance in Nepal: A Long-Run Relationship Analysis - Shrestha, Jamuna; Adhikari, Gyan Mani; Bhusal, Bijaya (Academia Journal of Research and Innovation, 2026)
The study examines the long-run relationship between remittances and current-account balance in Nepal between the year 1975 and 2024 using a Vector Error Correction Model (VECM). It is based on the annual observations of the current-account balance, remittance inflows, trade openness, real GDP growth, foreign direct investment and inflation rate. The cointegration test by Johansen establishes the relationships of long-run equilibrium between the variables. The results of VECM show that remittances have a statistically significant positive impact on the current-account balance in the long term, but trade openness has been negative. The mechanism of error-correction discloses that about 26.8 per cent of short-run disequilibrium is corrected in a year. The Granger-causality tests indicate that there is a two-way causal relationship between remittances and the current-account balance, whereas there is a one-way causal relationship between GDP growth and the current-account balance. These results imply remittance inflows are a critical external source of finance in Nepal and improve the current account balance and stabilises the external sector.